Thrombocytopenia in a Patient Undergoing Primary Percutaneous Coronary Intervention - Oktaviono, Yudi Her; Meuthia, Feranti (Folia Medica Indonesiana, 2019)
Thrombocytopenia is a common abnormality in patients presenting with acute coronary syndrome. Baseline thrombocytopenia in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention is associated with early adverse events, related to both ischemia and bleeding. Treatment for acute coronary syndrome usually involves antiplatelet, anticoagulant, antithrombotic therapy, and the performance of percutaneous coronary intervention. The safety of antiplatelet therapy and percutaneous coronary intervention patients who have acute coronary syndrome and thrombocytopenia is unknown, and there are no guidelines or randomized studies that specifically suggest a treatment approach in such patients. One of the institutions in Italy recommends medical and interventional strategy with radialis as first choice for access site, bare metal stent (BMS) implantation, followed by double antiplatelet therapy (DAPT) for one month. After DAPT discontinuation, at least one antiplatelet drug (aspirin) is recommended for life.